2011
DOI: 10.1097/prs.0b013e3181fed560
|View full text |Cite
|
Sign up to set email alerts
|

Does Previous Chest Wall Irradiation Increase Vascular Complications in Free Autologous Breast Reconstruction?

Abstract: Prereconstruction radiation therapy increases the rate of vascular complications in free flap breast reconstruction, the majority of which appear intraoperatively. Although radiation does not hinder the overall success of reconstruction or contribute to postoperative complications, surgeons should be aware that working in a previously irradiated field carries additional technical risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 33 publications
0
75
2
3
Order By: Relevance
“…Fosnot et al [13], studying the effect of previous radiation on vascular complications after free autologous breast reconstruction, with a total of 1025 free flaps, found an increase in acute complications and added technical difficulties during surgery, but with no significant long-term negative implications for the reconstructive outcome [13].…”
Section: Discussionmentioning
confidence: 98%
“…Fosnot et al [13], studying the effect of previous radiation on vascular complications after free autologous breast reconstruction, with a total of 1025 free flaps, found an increase in acute complications and added technical difficulties during surgery, but with no significant long-term negative implications for the reconstructive outcome [13].…”
Section: Discussionmentioning
confidence: 98%
“…This is borne out by the abundant literature that describes significantly more complications in any type of reconstruction of the irradiated breast. [22][23][24][25][26][27][28][29][30][31][32][33][34] The most valuable reports would be those that include both irradiated and nonirradiated breasts but that go on to segregate the data based on the timing of breast irradiation. The same is true regarding two-stage breast reconstruction with tissue expanders as opposed to one-stage direct-to-implant reconstruction.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5] Our group previously demonstrated that there is a significant increase in intraoperative microvascular complications in patients who have undergone radiation before free flap breast reconstruction, but no difference in postoperative complications or major outcomes. 6 Although this was a well-designed study that controlled for multiple factors including concurrent chemotherapy and patient comorbidities, this examination was performed looking specifically at flap complications and issue per flap, including bilateral and unilateral patients.…”
mentioning
confidence: 99%